Chemical engineering systems modeling and efficiency analysis of heat and mass exchange - Yakovleva, Olga; Yakovlev, Yuriy; Toumanskiy, Viktor (Technology audit and production reserves, 2017)
The object of research is the chemical engineering system and the heat-mass exchange processes taking place in it. In engineering practice, systems are represented by process flow diagrams. The lack of standardization in the graphical representation of engineering systems does not allow creating a general logic for reading the graphic information and then processing it with the software for analyzing the energy efficiency of the chemical engineering system. The rules for creating flowcharts, symbols for devices, and the chemical engineering system representation technique are developed, allowing any engineering system to be transformed into its topological representation. To combine the two branches of different networks and organize the heat and mass exchange processes in the system are elements intended for heat and energy exchange between networks with streams pair interaction. Mathematical models of heat and mass exchange networks for chemical industry have been developed, and energy efficiency and mass transfer efficiency criteria have been introduced. This allows to: construct a software environment that generates a system model based on its topological representation; analyze various options for implementing the process flow diagram for finished products production; synthesize the optimal, energy-saving production option. A numerical experiment was performed using a modeling software developed by the German company NETWORK SOLUTION DEVELOPMENT CO and transferred for testing. The model adequacy to the real engineering system approves the comparison of the model parameters and the parameters of the design regime of the urea production synthesis unit. The error in determining the mass flow rates doesn’t not exceed 2.4 % on branches, and the temperatures values at the nodes are strictly correspond to the technological regulations. Preliminary analysis indicates the possibility of improving the energy efficiency of production due to the integration of heat streams within the production cycle and the structural and parametric optimization of the engineering system.